THE ROLE OF LINGUCULTURAL COMPETENCE IN FOREIGN LANGUAGE LEARNING (Global Conference on Multidisciplinary Research and Innovation, 2026)
This thesis examines the role of lingucultural competence in foreign language learning and explains why successful language acquisition cannot be limited to grammar, vocabulary and pronunciation. Lingucultural competence is understood as the learner’s ability to understand, interpret and use language in connection with cultural meanings, social norms, values, traditions and communicative behavior. The thesis argues that foreign language learning becomes more effective when linguistic knowledge is integrated with cultural awareness, because language reflects the worldview of its speakers. The study is based on theoretical analysis of linguistic, cultural and pedagogical sources. The findings show that lingucultural competence improves communicative accuracy, reduces intercultural misunderstanding and develops learners’ ability to participate in real communication.
Keywords: lingucultural competence, foreign language learning, intercultural communication, cultural awareness, communicative competence, language teaching.